FROM OBSERVATION TO COMPOSITION: OUTDOOR CLASSROOM ACTIVITIES IN ENHANCING EFL STUDENTS’ DESCRIPTIVE WRITING SKILLS - Safrudin Sahmadan; Hariyantidj Hariyantidj (Tadulako University, 2026)
Writing is one of the most challenging skills for English as a Foreign Language (EFL) learners, particularly in producing descriptive texts that require students to generate ideas, organize information, and use appropriate vocabulary. Despite the growing emphasis on student-centered learning, many EFL classrooms continue to rely on conventional instructional approaches that provide limited opportunities for authentic learning experiences. Therefore, this study aimed to investigate the effectiveness of outdoor classroom activities in improving students’ descriptive writing ability. This study employed a quantitative approach using a pre-experimental one-group pre-test and post-test design. The research was conducted at Junior High School North Maluku and involved 33 eighth-grade students selected through purposive sampling. Data were collected through writing tests administered before and after the implementation of outdoor classroom activities. The obtained data were analyzed using descriptive statistics and a t-test to determine the significance of students’ improvement. The findings revealed a substantial increase in students’ writing achievement. The mean score improved from 47.48 in the pre-test to 68.55 in the post-test, with a gain of 21.07 points. Furthermore, the calculated t-value (4.795) was higher than the critical t-value (2.037) at the 0.05 significance level (df= 32) indicating a statistically significant improvement in students’ descriptive writing performance. In conclusion, outdoor classroom activities represent an effective instructional strategy for improving EFL students’ descriptive writing ability. The study highlights the pedagogical value of integrating authentic learning environments into writing instruction to support more contextualized and meaningful language learning experiences.